Amended identification of Oxydia (Lepidoptera: Geometridae) on Brazilian peppertree. Issue 4 (3rd April 2019) - Hayden, J. E.; Wheeler, G. S.; Dyer, K.
ABSTRACT: A colony of moths recently studied and published for control of Schinus terebinthifolia is found not to be Oxydia vesulia (Cramer) but instead a possibly undescribed species. Three species were originally collected. The unknown species is diagnosed by morphology and COI and compared to congeners.